Minerva's owl : the tradition of western political thought - Abramson, Jeffrey B. (Harvard University Press, 2009)
"Jeffrey Abramson argues politics with the classic writers and draws the reader into a spirited conversation, with contemporary examples that illustrate the enduring nature of political dilemmas. As the discussions deepen, the voices of Abramson's own teachers, and of the students he has taught, enter into the mix, and the book becomes a tribute not just to the great philosophers but also to the special bond between teacher and student."--Jacket.